You are not I - Bowles, Paul 1910-1999; Kline, Phil 1953-
"A young woman escapes from a mental hospital during the chaos of a nearby multiple-car accident. She is mistaken for a shock victim and is driven to her sister's house by a rescue volunteer... [imdb.com]
Original: USA 1981
Bildformat 1.33:1 (4:3)